2020
DOI: 10.3390/foods9091325
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes towards Local and Organic Food with Upcycled Ingredients: An Italian Case Study for Olive Leaves

Abstract: Food made with upcycled ingredients has received considerable attention in very recent years as a result of the need to both reduce waste and increase food nutritional properties. However, consumer acceptance of these novel foods is fundamental to their market uptake. This paper aims to assess the likelihood of the acceptance of food obtained from upcycled ingredients of olive oil productions and its association with some relevant recent consumption trends, such as organic food consumption and attention to foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 65 publications
(102 reference statements)
4
38
0
Order By: Relevance
“…However, our results pointed out that even when consumers profess a strong support for environmental attributes, they are still extremely price sensitive. These findings are in line with the literature related to the consumer' approach to the decision to purchase sustainable food [18,55,56].…”
Section: Resultssupporting
confidence: 90%
“…However, our results pointed out that even when consumers profess a strong support for environmental attributes, they are still extremely price sensitive. These findings are in line with the literature related to the consumer' approach to the decision to purchase sustainable food [18,55,56].…”
Section: Resultssupporting
confidence: 90%
“…Concurrently, in the last three years, a small body of academic literature has also emerged. Studies conducted in the United States and Europe show that consumer acceptance for upcycled foods can be shaped by understanding and guiding consumers' evaluation of these foods [2][3][4][5][6][7]11,13,15]. The findings of this study reinforce emerging awareness and positive consumer sentiments about upcycled foods.…”
Section: Discussionsupporting
confidence: 61%
“…The current research advances the literature on upcycled foods on three fronts. First, while there have been studies on consumer perceptions of upcycled foods in the United States [1][2][3][4]9] and Europe [5][6][7][10][11][12][13][14], this research is the first with shoppers in New Zealand. Second, most research on this topic has relied on small samples in laboratory-like settings.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, in recent years, have been carried out in the context of new and diversified trends of EVOO consumer demand [ 44 , 45 , 46 , 53 , 55 , 58 ], and different surveys have shown that consumers’ choices widely differ with respect to sensory preferences, extrinsic quality signals, experience, purchase motives, perception of supply elements, and socioeconomic characteristics [ 47 , 59 , 60 , 61 , 62 ]. Moreover, the literature results indicate that organic certification, origin of both olives and olive oil, and price are the main extrinsic attributes of EVOO guiding the choice process of consumers [ 68 , 69 , 70 , 76 , 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, several authors highlight the relevance of the organic attributes of EVOO and their importance to consumers, in particular, Tsakiridou et al [ 62 ], Liberatore et al [ 68 ], Roselli et al [ 69 ], and Perito et al [ 70 ]. Most of the themes also investigate organic and origin attributes together.…”
Section: Introductionmentioning
confidence: 99%